Informes en la familia Pteridaceae (Filicales) para el Neotrópico - Rojas – Alvarado, Alexander Fco (Revista de Biología Tropical, 2001)
Several contributions to the Neotropical pteridophyte flora are made in this paper with the range extensions for four species of Adiantum, two species of Doryopteris and one species of Eriosorus. The species concerned are: A. polyphyllumWilld. for Nicaragua and Costa Rica; A. trichochlaenum Mickel et Beitel for Guatemala and Costa Rica; A. villosissimum Mett. ex Kuhn for Costa Rica; A. wilesianum Hook. for Nicaragua; D. nobilis (T. Moore) C. Chr. for Costa Rica, Colombia and Venezuela; D. redivida Fée for Panama; and E. hirtus (Kunth) Copel. for Costa Rica. The concept of D. pedata (L.) Fée is redefined.